2015
DOI: 10.1523/jneurosci.3760-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Competition Is Modulated by Sensory Pathway Interactions with Fronto-Sensorimotor and Default-Mode Network Regions

Abstract: Multisensory information competes for preferential access to consciousness. It remains unknown what neural processes cause one particular modality to win multisensory competition and eventually dominate behavior. Thus, in a paradigm in which human participants sought to make simultaneous auditory and visual detection responses, we sought to identify prestimulus and poststimulus neural signals that were associated with auditory and visual dominance on each trial. Behaviorally, visual detection responses precede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 40 publications
(6 reference statements)
4
77
0
Order By: Relevance
“…There are two main types of behavioral outcomes to multisensory integration. The first type are multisensory illusion effects, which involve merging of information across senses; in some cases, one sensory modality within the multisensory information competes for preferential access to the consciousness, which means that this modality dominates the others to receive preferential processing during multisensory competition and eventually dominates the awareness and behavior of the observer (Stein and Meredith, 1993;Driver and Noesselt, 2008;Koelewijn et al, 2010;Talsma et al, 2010;Spence, 2011;Chen and Zhou, 2013;Huang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There are two main types of behavioral outcomes to multisensory integration. The first type are multisensory illusion effects, which involve merging of information across senses; in some cases, one sensory modality within the multisensory information competes for preferential access to the consciousness, which means that this modality dominates the others to receive preferential processing during multisensory competition and eventually dominates the awareness and behavior of the observer (Stein and Meredith, 1993;Driver and Noesselt, 2008;Koelewijn et al, 2010;Talsma et al, 2010;Spence, 2011;Chen and Zhou, 2013;Huang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that the modulation of both amplitude and phase of EEG oscillation could be important mechanisms to enable cross-modal interactions [ 7 9 ]. In addition, a recent EEG and fMRI study showed that when there is competition between visual and auditory stimuli, requiring active endogenous control of attention, there is modulation of activity within the sensory cortices, sensorimotor areas and the default mode network (DMN) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DMN is involved in affective regulation and internal thoughts (14)(15)(16), showing major changes in psychiatric illnesses, such as BD (17)(18)(19)(20)(21), and major depressive disorder (22)(23)(24). At the same time, the DMN may be related to psychomotor behavior through its relationship with the sensorimotor network (10). Because of the co-occurrence of alterations in affect, thought, and psychomotor behavior in BD, based on existing evidence one could hypothesize abnormal relationships-topographical patterns in the balances between these networks-especially between the DMN and SMN (10) (considering the central clinical role of psychomotor…”
mentioning
confidence: 99%